2019
DOI: 10.1371/journal.pone.0221179
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis revealed the co-circulation of four dengue virus serotypes in Southern Thailand

Abstract: Dengue fever is caused by dengue viruses (DENV) from the Flavivirus genus and is the most prevalent arboviral disease. DENV exists in four immunogenically distinct and genetically-related serotypes (DENV-1 to 4), each subdivided in genotypes. Despite the endemicity of all four DENV serotypes in Thailand, no prior study has characterized the circulation of DENV in the southern provinces of the country. To determine the genetic diversity of DENV circulating in Southern Thailand in 2015 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 53 publications
5
51
3
Order By: Relevance
“…In Lao PDR, Asian I and Cosmopolitan genotypes have been co-circulating since at least 2017 and was still ongoing in 2019. Compared to a recent study in Thailand, our series identified different lineages within the DENV-2 Cosmopolitan genotype [43]. Indeed, in Thailand only the Cosmopolitan genotype/Lineage B was observed between 2015 and 2016.…”
Section: Plos Onecontrasting
confidence: 73%
See 3 more Smart Citations
“…In Lao PDR, Asian I and Cosmopolitan genotypes have been co-circulating since at least 2017 and was still ongoing in 2019. Compared to a recent study in Thailand, our series identified different lineages within the DENV-2 Cosmopolitan genotype [43]. Indeed, in Thailand only the Cosmopolitan genotype/Lineage B was observed between 2015 and 2016.…”
Section: Plos Onecontrasting
confidence: 73%
“…Indeed, in Thailand only the Cosmopolitan genotype/Lineage B was observed between 2015 and 2016. As seen elsewhere, since 2008 the Lao clusters within the Asian I genotype have had different geographic origins and evolved over time as independent topotypes as is seen on other countries [4,43,50]. In a panel tested previously and in this study, the co-circulation of two or three clusters were observed in 2009-2010 (cluster 1, 2 and 3), in 2012 (clusters 3 and 5), in 2017 (clusters 4 and 6) and in 2018 (clusters 4 and 7).…”
Section: Plos Onementioning
confidence: 72%
See 2 more Smart Citations
“…An ideal dengue antiviral must significantly reduce the viral load within 70 h of illness onset to prevent disease progression to DHF or DSS [24]. Furthermore, the drug should inhibit all four DENV serotypes as these serotypes could co-circulate in endemic areas [25,26].…”
Section: Current Status Of Dengue Antiviral Developmentmentioning
confidence: 99%